PENELUSURAN POLA SPASIAL WILAYAH MILITER DI KOTA MAGELANG (Jurnal Arsitektur ARCADE, 2026)
This study aims to identify function based military spatial relationships in Magelang City, Indonesia. Zoning is a rule of spatial distribution in urban areas that functions to regulate land use to create a more orderly environment. This study attempts to identify various forms of function-based spatial relationships related to military zones. Military zones have traditionally been associated with security and defense systems, but in Magelang City, they appear as part of the urban space. This identification has the potential to be used to expand knowledge regarding military spatial patterns that are connected to zoning. The emergence of function-based zoning patterns can enrich knowledge of urban design. This research method is qualitative, focusing on the military area in Magelang City. Data were collected through field observations, documentation, and location map processing to identify spatial patterns and their relationships. The results of this study indicate the presence of nine spatial patterns and demonstrate the inseparable spatial relationships in military areas, this allows for a different understanding of urban zoning. The residential function is the most dominant element because it is connected to almost all other main functions.
Keywords: distribution of military functions, zoning, connectivity, territory